Analisis Penentuan Pusat-Pusat Pertumbuhan (Growth Pole) dan Wilayah Belakang (Hinterland) Provinsi Kalimantan Tengah - Dwi Ardi Wicaksana Putra; Depi Rusda; Abdul Aziz (Ecoplan, 2020)
Abstract - The purpose of this study is to determine one or more regency/municipality as the growth poles and its hinterlands in Kalimantan Tengah Province to solve the welfare’s imbalance occurs. This study is descriptive research with the quantitative approach and carried out in a purposive manner in Kalimantan Tengah Province. The secondary data of this study were based on the BPS source in 2014-2018. Including Gross Regional Domestic Product (GRDP) at 2010 Constans Market Prices, Human Development Index (HDI) by Regency / Municipality, and the distance between regency/municipality in Kalimantan Tengah Province. The data analysis method used the Klassen Typology approach and the gravity model analysis. This study presents the changes in the regency/municipality's economic activities through each year's calculation analysis, which becomes the growth poles in Kalimantan Tengah Province. This study shows that the growth poles in Kalimantan Tengah Province are Palangkaraya City, Kotawaringin Timur, Kotawaringin Barat, and Gunung Mas Regency, well as their various rear regions. Moreover, this study provides the contribution which proves that the ranking of an area that has the same classification (through the Klassen Typology method by including the HDI variable) based on the achievements of experience per year of analysis, it is declared to have represented and being able to maintain the potential attractiveness or trade relationships on each region. Keywords: Growth pole, hinterland, Klassen Tipology, gravity model analysis, trade